Transitions outside the mainstream: Stories of children and their families. Issue 1 (March 2019) - Warren, Jane; Harden-Thew, Kathryn
Smooth transitions through the early years of education are recognised as pivotal to later personal and academic success. However, for children considered outside the mainstream, these transitions can provide extra challenge for them, their families and educators. This paper reveals the findings of two qualitative studies investigating early years' transitions. The first study focused on the transition of children with disabilities into early childhood education and care (ECEC) centres; the second explored transition to school for emergent bilingual children. These studies highlight 'strengths-based' perspectives (Perry, Dockett, & Petriwskyj, 2013), wherein participants are understood as experts in their own lives bringing strengths as well as challenges to the new context. Despite the differences in participants, timing and methods, key themes were evident across the studies: parent perceptions of transition; educator attitudes; and home/centre or home/school relationships. These themes are significant to all educational transitions for children considered outside the mainstream.